Drought immediately increases soluble sugar and decreases starch in seedlings of the shade-tolerant compared to the sun-tolerant ecotype of Paubrasilia echinata - Cuzzuol, Geraldo Rogério Faustini; Fonseca, Carlos Luis Sánchez; de Moraes, Moemy Gomes; Macieira, Bernardo Pretti Becacici (Flora. Morphologie, Geobotanik, Oekophysiologie, 2025)
•Drought affected the starch (aerial organs) of shade-tolerant more than sun-tolerant ecotype of P. echinata.•Shade-tolerant ecotypes were more sensitive to drought, requiring greater NSC and CWP adjustments.•These responses may hinder plant functioning under intensified droughts. How shade-tolerant and sun-tolerant plants will respond to the predicted increase in drought for tropical forests by the end of this century is a subject of global interest. One of the physiological defense mechanisms of plants against the harmful effects of drought is their ability to adjust their contents of non-structural carbohydrates – NSC (soluble sugars and starch) and cell wall polymers – CWP (hemicelluloses, cellulose, and lignin). As a research model, we used plants of the small leaf (shade-tolerant) and medium leaf (sun-tolerant) ecotypes of Paubrasilia echinata, a tree native to the Atlantic Forest of Brazil. The plants were subjected to drought (no watering) for 17 days when the water potential (Ψw) of the leaves reached -3 MPa. Then, they were watered daily (rehydration) for 36 days. In different periods, we evaluated the NSC and CWP contents of their leaves, stem, and roots. Intraspecific similarities and divergences occurred in the contents of these molecules. The shade-tolerant ecotype showed immediate responses to drought by raising the soluble sugar and hemicelluloses, and decreasing the starch contents (aerial organs). The lignin content increased in the aerial organs of both ecotypes and the cellulose content more in the sun-tolerant ecotype. After rehydration, the NSC and CWP contents of the two ecotypes were equal to their controls. We concluded that the shade-tolerant ecotype showed greater sensitivity to drought by demonstrating a greater need for NSC and hemicelluloses adjustments at the beginning of the drought. However, the drought did not affect the survival of the two ecotype's plants. If climate change forecasts for the southeastern region of Brazil prevail in the coming decades, natural or planted seedlings of the shade-tolerant ecotype of P. echinata may suffer greater consumption of its transient energy reservoir (starch). Such responses can compromise the functioning of their seedlings if droughts become more intense and frequent.